INTERNATIONAL LEGAL STANDARDS FOR THE PROTECTION OF THE DEFENDANT’S RIGHT TO A FAIR TRIAL (Eurasian Journal of Law, Finance and Applied Sciences, 2026)
This article analyzes international legal standards for ensuring the right of the accused to a fair trial. It examines key procedural guarantees established in the Universal Declaration of Human Rights, the International Covenant on Civil and Political Rights, the European Convention on Human Rights, and the Rome Statute. Particular attention is paid to the presumption of innocence, the right to defense, the right to a fair trial, and the principle of habeas corpus. The article also explores the practice of international judicial bodies in applying these standards. It substantiates the importance of protecting the rights of the accused within both national and international legal systems.